EM Forster's will: an overlooked posthumous publication. (27th December 2012) - Monk, Daniel
<x xml:space="preserve">Abstract</x> Focusing on a single, uncontested will is unusual within legal studies. And the extensive literature about EM Forster has overlooked the significance of his will. This article endeavours to address these silences and develop a conversation between the two. It first explores the place of inheritance in Forster's life and novels; and in doing so highlights his interest in inheritance as both a concept and a practice. Turning then to his will, it argues that it reveals a reflective personal and political engagement with concerns about kinship, sexuality and intimate citizenship which are central to current debates within socio‐legal and sociological scholarship. This reading consequently argues that his will is a text that can be read alongside his other work; that it represents a 'posthumous publication'. While a close, critical reading of the will of one very particular individual, the article identifies the challenges posed to testators in negotiating the public and private nature of wills and highlights both the rich potential and the difficulties that these texts present for socio‐legal, literary and biographical scholarship.